Oral administration of a potassium bromate dosage: Determination and evaluation of accumulated bromate on the liver of male mice. (2nd January 2022) - Germoush, Mousa Othman; Alsohaimi, Ibrahim Hotan; Alqadami, Ayoub Abdullah; Alothman, Zeid Abdullah; Ali, Hazim Mohammed; Algamdi, Mohammad Saad; Aldawsari, Abdullah Mohammed
Abstract: In this work, we developed a simple spectrophotometric strategy for BrO3 − ions determination as a major water disinfection constituents in the mice's liver tissues by using pararosaniline (PRA). Mice were divided into seven main groups (6 doses): lowest dose KBrO3 (G1 0.01 mg L −1, G2 0.025 mg L −1 and G3 0.1 mg L −1 ), highest dose KBrO3 (G4 1 mg L −1, G5 10 mg·L −1 and G6 30 mg L −1 ) and control. All these groups maintained a dose-specific feeding for one month, just before the bromate assessment in mice's liver samples. The results revealed that groups of exposure to lower doses of drinking water did not detect the presence of BrO3 − accumulated in the liver tissue during the study period (1–2 months). While, the BrO3 − was detected in higher dosages for samples analyzed in first, second, third, fourth and fifth weeks (W1, W2, W3, W4, and W5 ). These results confirmed that the higher BrO3 − dosages (1, 10, and 30 mg L −1 ) were fatal if introduced in drinking water and could accumulate in the liver tissues both for mice and for human. Detection the accuracy of the method for recovery of bromate ions in liver samples ( N = 5) was found to be more than 95%. Relative standard deviations (RSDs) were found to be less than 2.0% confirming the reproducibility of the assay technique.